ANALISIS PENGARUH BIOLOGICAL ASSET INTENSITY DAN PROFITABILITAS TERHADAP PENGUNGKAPAN ASET BIOLOGIS PADA PERUSAHAAN AGRIKULTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018 - Sindi Elis Sakinatunnisak; Kim Budiwinarto (Universitas Slamet Riyadi, 2020)
This research aims to examine and analyze the effect of biological asset intensity and profitability on the disclosure of biological assets in agricultural companies that are leveled on the Indonesia Stock Exchange (BEI) in 2018. This research is a quantitative case study. Secondary data obtained by the documentation method. The sample of this research was 18 agricultural companies listed on the Indonesia Stock Exchange in 2018. Eighteen companies met the criteria. They registered and published financial statements in the 2018 period. Data analysis techniques use descriptive statistical analysis, multiple linear regression analysis, ttest, F-test, and coefficient of determination. The results showed that biological asset intensity has a significant effect on the disclosure of biological assets in agricultural companies listed on the Indonesia Stock Exchange in 2018, and profitability has a significant effect on the disclosure of biological assets in agricultural companies listed on the Indonesia Stock Exchange in 2018.